A escola na condição de não lugar - Silva, Antonio Carlos Barbosa da [UNESP]; Silva, Marina Coimbra Casadei Barbosa da [UNESP] (My University, 2012)
This article portrays the changes that schools and education have been undergoing since the Middle Ages to the contemporary era. Its main focus points at the subjective issues that underlie the school as educational space necessary for the maintenance of society. It ends by showing that the school currently is losing its historical, relational and identity function (essential issues to structure a society) and is becoming a non place (concept of Marc Augé), into an institution without apparent social function, held only as a still a consumable and profitable commodity.

O presente artigo retrata as transformações que a escola e a educação vêm passando desde a idade média até a era contemporânea. Tem como foco principal apontar as questões subjetivas que fundamentaram a escola enquanto espaço educativo necessário à manutenção da sociedade. Finda por mostrar que a escola, atualmente, está perdendo sua função histórica, identitária e relacional (questões essenciais para estruturar uma sociedade) e está se transformando em um não lugar (conceito de Marc Augé), em uma instituição sem função social aparente, mantida apenas por ainda ser uma mercadoria consumível e lucrativa.
The school as a no place
Keywords: No Place; Education; School; Contemporary; Augé; Não Lugar; Educação; Escola; Contemporaneidade; Augé